Ludovico Quaroni and the Anagnina residential district (1985) (L'architettura delle città - The Journal of the Scientific Society Ludovico Quaroni, 2013)
When Quaroni was given the job of designing the Anagnina district early in 1984, as part of the Rome Piano di Edilizia Economica e Popolare (PEEP: the Centralised Public Housing Plan), he must have been somewhat puzzled by the vagueness and imprecision of the task he was supposed to perform. He himself expressed this perplexity on behalf of his group, when in the Introduction to the Technical Report on the project, he said that «for many of us, the initial requests of the City Council were not at all clear, and the exact direction in which we were expected to work was particularly imprecise». Quaroni was unquestionably quite right in harbouring some doubts, and this time not only relying on his own ‘method’ and his proverbial intellectual talents. As the leader of a group of young Roman architects he found himself charged with carrying out an extremely responsible undertaking, in the form of designing a public-enterprise residential area whose requirements were only described in general terms.